Implementation of Discretion Perspective of Penal Policy (Study of Yogyakarta Police Department) - Ikbal, Muhammad (Universitas Negeri Semarang, 2018)
The purpose of this research is to know the regulation of police discretion of Yogyakarta special region in criminal law enforcement and how to apply police discretion in criminal law enforcement in terms of penal policy aspect. The implementation of the special police discretion of the special region of Yogyakarta is guided by the provisions of written rules and unwritten rules that live in the community and is guided by the lines of criminal law policy. The application of the special area police discretion of Yogyakarta can be applied by investigators and investigators through restorative justice approaches in certain cases, the settlement in this way is a form of protection to both the perpetrator and the victim in order to reach a peace agreement.